Cloning of the cDNA for the TATA-binding protein-associated factor(II)170 subunit of transcription factor B-TFIID reveals homology to global transcription regulators in yeast and Drosophila - van der Knaap, Jan A. (The National Academy of Sciences of the USA, 1997)
The human transcription factor B-TFIID is comprised of TATA-binding protein (TBP) in complex with one TBP-associated factor (TAF) of 170 kDa. We report the isolation of the cDNA for TAF(II)170. By cofractionation and coprecipitation experiments, we show that the protein encoded by the cDNA encodes the TAF subunit of B-TFIID. Recombinant TAF(II)170 has (d)ATPase activity. Inspection of its primary structure reveals a striking homology with genes of other organisms, yeast MOT1, and Drosophila moira, which belongs to the Trithorax group. Both homologs were isolated in genetic screens as global regulators of pol II transcription. This supports our classification of B-TFIID as a pol II transcription factor and suggests that specific TBP–TAF complexes perform distinct functions during development.